Stereoselective formation of coordination polymers with 1, 4-diaminonaphthalene on various Cu substrates1. Issue 54 (11th July 2015) - Knor, Marek; Gao, Hong-Ying; Amirjalayer, Saeed; Studer, Armido; Gao, Hongjun; Du, Shixuan; Fuchs, Harald
<x xml:space="preserve">Abstract</x> Controlled polymerization of 1, 4-diaminonaphthalene on various Cu crystallographic planes (111), (110) and (100) resulting in stereoselectively well-defined metal–organic coordination polymers.